Comparison Between Rasm Utsmani and Rasm Imla’i in Relation to the I’jazul Al-Qur’an : (Komparasi Antara Rasm Utsmani dan Rasm Imla’i Terhadap I’jazul Qur’an) - Umam, Ahmad Mualim; Nurusshobah, Nurusshobah (Al Muhafidz: Jurnal Ilmu Al-Qur'an dan Tafsir, 2025)
This study examines the unique features of Rasm Utsmani and Rasm Imla’i, highlighting the ways these writing systems support the concept of i‘jaz Al-Qur’an, particularly in terms of their influence on meaning, word structure, and the aesthetic qualities of the Qur’anic language. Using a qualitative-descriptive method, the study conducts textual analysis on selected Qur’anic verses that exhibit orthographic differences between the two scripts. The data were collected through literature review, encompassing canonical mushaf, classical Qur’anic sciences, and contemporary scholarly discussions. The analysis reveals that Rasm Utsmani functions beyond a mere orthographic convention it carries symbolic layers that convey profound meanings and support the Qur’an’s miraculous nature. While Rasm Imla’i prioritizes phonetic clarity for ease of reading and writing, it tends to lack the visual depth and exegetical richness present in Rasm Utsmani. The study suggests that integrating both systems in Qur’anic pedagogy balancing readability with a deeper appreciation of divine linguistic structure can enhance comprehension and spiritual engagement with the text.